The neighbor as a theological cultural place - Contreras Opazo, Andrés (Cuadernos Judaicos, 2020)
This article calls for awareness of the existence of the neighbor in a diverse society in which human groups that develop in diverse cultural spheres coexist and calls for a behavior of approach from otherness, which allows an inclusive and tolerant relationship in a postmodern society whose characteristic is essentially given by individuality and preferably human relationships "of convenience". Neighbor is the one who is close and close, the relationship with him will bring endless relationships also with the cultural sphere of a nation and how this neighbor unfolds in an intracultural, intercultural and transcultural sphere.